2012
DOI: 10.1097/wnr.0b013e32835abc5c
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness of supratemporal plane predicts auditory N1 amplitude

Abstract: The auditory-evoked potential's N1 component of the scalp electroencephalogram is a well-established measure of electrical brain activity. The N1 reflects basic auditory processing and is modulated by auditory experience, for instance, by musical training. Here, we explore a possible correlation between the auditory N1 amplitude and cortical architecture in the supratemporal plane. We hypothesize that individual differences in N1 amplitude reflect differential acuity, which might also be reflected by differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The primary source of N1 and P2 is the auditory cortex (35, 36) (Heschl's gyrus); we identified reduction in gray matter regions surrounding this structure. Parietal target N2 in E2 was significantly increased (reduced change from baseline) in probands indexing abnormal stimulus classification (37).…”
Section: Discussionmentioning
confidence: 87%
“…The primary source of N1 and P2 is the auditory cortex (35, 36) (Heschl's gyrus); we identified reduction in gray matter regions surrounding this structure. Parietal target N2 in E2 was significantly increased (reduced change from baseline) in probands indexing abnormal stimulus classification (37).…”
Section: Discussionmentioning
confidence: 87%
“…Structural measures reflecting auditory experience and development, such as the cortical thickness of Heschl’s Gyrus in auditory cortex, have also been correlated with the N1 response (Fu and Zuo, 2011; Liem et al, 2012). As children age through pre-adolescence, region-dependent decreases in gray matter volume occur, concurrent with white matter volume increases, possibly providing a structural basis for developmental changes reported for the N1 CAEP (Gogtay et al, 2004; Group B.D.C., 2012; Lenroot and Giedd, 2006; Muftuler et al, 2011).…”
Section: Central Auditory Development In Deafnessmentioning
confidence: 99%
“…Since the P1 response complex may include not only primary activation but also, to a minor proportion, early secondary pitch‐sensitive responses of lateral HG (Yvert et al, ; Schneider et al, ), it is important to separate the earlier primary component by appropriate constraints (Schneider et al, ; Wengenroth et al, ). In a combined MRI and EEG study, Liem, Zaehle, Burkhard, Jancke, and Meyer () have reported thinner CTH to be associated with larger N1 amplitude in lateral HG. Furthermore, it is well‐known that auditory response patterns differ between children and adults under influence of maturational learning processes.…”
Section: Introductionmentioning
confidence: 99%